Characterization of volcanic ashes deposited in Puebla City - Cruz-Sánchez, Misael; Cruz-Santos, Mildred; Ángeles-García, Sonia; Girón-García, Patricia (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2021)
Puebla City is located 40 km east of the Popocatepetl volcano, being the frequent destination of volcanic ash that travels in a southeast-northeast direction towards the metropolitan area. A series of ash collected in the years 2012, 2015, 2016, 2017, and 2019 have been characterized by texture, mineralogy, and leaching tests in deionized water. The results establish that the texture of the deposited ashes varies from silty sand to sand, being classified as unaltered non-porous coarse ashes. The ashes have an andesitic composition with plagioclase (70-80%) and pyroxenes (20-25%) as main minerals, highlighting that in plagioclase an anorthite albitization process is identified. The analysis of the leached components has defined two facies Ca-Mg-HCO3 and Ca-Mg-Cl and/or Ca-Mg-SO4, with As, Al, and Fe as main trace elements, whose origins are associated with partial dissolution of plagioclase and pyroxenes promoted by magmatic or hydroclastic gases.